Effects of Currency Unions on Foreign Direct Investment Inflows: The European Economic and Monetary Union Case - KILIC, Cuneyt; BAYAR, YILMAZ; ARICA, Feyza (International Journal of Economics and Financial Issues, 2013)
Reducing exchange rate and inflation, transaction costs and achieving the economic convergence among member countries are major causes of establishing a monetary union. This paper examines the effects of European Economic and Monetary Union on inflows of foreign direct investments to the Eurozone by using panel data from 16 Group of 20 countries for the period 1999-2012. We found that real GDP, GDP growth rate and exchange rates of 16 Group20 countries affect inflows of real foreign direct investment positively while exchange rate volatility, inflation volatility and distance affects inflows of real foreign direct investment negatively. So European Economic and Monetary Union contribute to the inflows of foreign direct investment by reducing the exchange rate volatility, inflation volatility and distance and supporting economic growth. Keywords: European Economic and Monetary Union; Group 20 Countries; Foreign Direct Investment; Panel Data Analysis. JEL Classifications: E42; F15; F36